Evidence-Based Midwifery Management of Premature Rupture of Membranes at Term Pregnancy in Primary Care: A Case Report - Aylinda Hrp; Riska Hutapea; Salwa Adya Mecca Saragih; Lydia Riska Dini Pinem; Ninsah Mandala Putri Sembiring; Modesta Marpaung (Asosiasi Dosen Muda Indonesia, 2026)
Premature Rupture of Membranes (PROM) is a common obstetric complication associated with maternal infection, neonatal morbidity, and adverse pregnancy outcomes if not managed promptly. Comprehensive and evidence-based midwifery care is essential to improve maternal and neonatal safety, particularly in primary healthcare settings. Objective: This case report aimed to describe the implementation of evidence-based midwifery management for a woman with term PROM using Helen Varney's Seven-Step Midwifery Management framework. Methods: A descriptive case report design was employed involving a 26-year-old primigravida (G1P0A0) at 39 weeks of gestation who presented with spontaneous rupture of membranes before the onset of regular uterine contractions. Clinical data were collected through patient interviews, physical and obstetric examinations, labor observations, medical records, and neonatal assessments. Data were analyzed descriptively using a narrative approach based on Helen Varney's Seven-Step Midwifery Management and interpreted according to current evidence-based recommendations. Findings: Following confirmation of PROM, continuous maternal and fetal monitoring was performed until spontaneous labor occurred. The patient delivered a healthy female infant vaginally with a birth weight of 3,000 g, body length of 49 cm, and an Apgar score of 9. The placenta was delivered completely, and the mother remained clinically stable despite experiencing a second-degree perineal laceration that was successfully repaired. No immediate maternal or neonatal complications were observed. Implications: The findings demonstrate that systematic assessment, continuous monitoring, and evidence-based midwifery management can support favorable maternal and neonatal outcomes in women with PROM and may strengthen the quality of maternity care in primary healthcare facilities. Originality: This report highlights the practical implementation of Helen Varney's Seven-Step Midwifery Management in a term PROM case within a primary healthcare setting, providing a structured example of evidence-based midwifery practice.